If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(7au) + u = 36 + u Remove parenthesis around (7au) 6 * 7au + u = 36 + u Multiply 6 * 7 42au + u = 36 + u Add '-1u' to each side of the equation. 42au + u + -1u = 36 + u + -1u Combine like terms: u + -1u = 0 42au + 0 = 36 + u + -1u 42au = 36 + u + -1u Combine like terms: u + -1u = 0 42au = 36 + 0 42au = 36 Solving 42au = 36 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '42u'. a = 0.8571428571u-1 Simplifying a = 0.8571428571u-1
| 3x-3(5-2x)=3 | | 8a^3+27b^3+64c^3=72abc | | 9(2X-1)=3(3x+3) | | 1p+2=-1 | | 3(2x+3)=2(3x+1) | | 2a^2-5a-4=0 | | 3u^2+12u+6=0 | | x(x-4)(x+11)=0 | | 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 | | 13x-30=7x-14 | | -6(x-3)=-3(x+9) | | (x-p)(x^2+11x+15)=(x^2-9)(2x+q) | | 2x^2-3-15=0 | | k+84738398=98393398 | | 8+9t=21t-17 | | X^2+.52x=-25 | | 3(b+4b)=40-15+20 | | -4(w-3)-6w=-2(w+6) | | 0=0.4t^2-7.7t+0.5 | | 0.2+10000= | | 3+9*2= |